FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN FREKUENSI KUNJUNGAN ANTENATAL CARE (ANC) DI PUSKESMAS MERGANGSAN PROVINSI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2014 - Vio Nita (Medika Respati : Jurnal Ilmiah Kesehatan, 2017)
Background : The direct causes of maternal death by 90% is a complication that occurs during labor and immediately after birth. One of the efforts to reduce maternal mortality is increasing coverage of antenatal care by health workers. Planning examination schedule (gestational age of the first day of the last menstrual period) ideal at least 8 times a visit. Preliminary study in Mergangsan public health centre in 2014 was found the visits data for the third trimester pregnant women in October - December 2014 that there were 158 pregnant women.Purpose : To study and analyze the factors associated with the frequency of visits Antenatal Care (ANC) in Yogyakarta Province Mergangsan public health centre in 2014.Methods : This study used quantitative research method with cross sectional approach and data collection on March 5 to May 5, 2015. The sample was taken by total sampling technique as much as 158 third trimester pregnant women. This research instrument using a questionnaire. Research data analysis using Chi-square analysis (p <0.05) and a simple logistic regression.Outcome : Pregnant women who visit antenatal care in many categories a number of 121 people (76.6%). Distribution according to knowledge (p value 0.027), attitude (p value 0, 003), age (p value 0.002), parity (p value 0,020), education (p value 0, 002), employment (p value 0.013), income (p value 0.013), distance (p value 0.176), resources (p value 0.000), the support of health professionals (p value 0.000), family support (p value 0.015) and the support of health professionals (p value 0.001) and the results of the simple logistic regression the dominant that support health workers (OR 12.282).Conclusion : The variables associated with the frequency of visits ANC ie knowledge, attitudes, age, parity, education, occupation, income, resources of information, support for health workers, family support, the support of community leaders. The variables are unrelated is the distance and the most dominant variable is the support of health professionals.Advice : Health workers to further improve in providing counselling to pregnant women about the importance of antenatal care to all pregnant women. Health workers can work together with the cadres in the counselling process. Keywords : Determinants frequency of antenatal care visits.Bibliography : 36 (2002-2012)